An Analysis on Risk Adjusted Performance and Asset Pricing Model Comparison in Indonesian Stock Market during Covid-19 - Kristio Rapi Tondok (Sekolah Tinggi Manajemen IPMI, 2022)
This study calculates the performance of the Fama and French Three Factor, the Carhart Four Factor, and the Fama and French Five Factor models and compares each performance using the Mean Absolute Deviant (MAD) and Ex-ante Sharpe ratio. The data is collected from Saham KOMPAS 100 for the period of 2017 to 2021, as well as calculations using Data Analytics tools in Microsoft Excel. The results are Factor model having the highest accuracy based on the value of Mean Absolute Deviant while the Three Factor model having the highest risk-adjusted return performance based on the Ex-ante Sharpe ratio. This study also pays attention to the context of the occurrence of COVID-19 in Indonesia, and based on the statistical analysis, this condition has a significant effect on stock returns. Keywords: Fama and French Three Factor Model, Carhart Four Factor Model, Fama and French Five Factor Model, COVID-19.